2015
DOI: 10.1007/s12032-015-0494-1
|View full text |Cite
|
Sign up to set email alerts
|

Crk-like adapter protein regulates CCL19/CCR7-mediated epithelial-to-mesenchymal transition via ERK signaling pathway in epithelial ovarian carcinomas

Abstract: Recent studies have suggested that Crk-like adapter protein (CrkL) and epithelial-to-mesenchymal transition (EMT) induced by CCL19/CCR7 play an important role in ovarian epithelial carcinogenesis. However, the regulatory mechanisms of CrkL on the CCL19/CCR7 signaling pathways in epithelial ovarian carcinomas (EOC) are not well characterized. Here, CCR7 and CrkL proteins were tested in 30 EOC tissues and cell lines. In vitro, the roles of CrkL in CCL19-stimulated SKOV-3 cell invasion and migration were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…CRKL amplification was previously observed in non‐small cell lung and gastric cancers, strongly suggesting that CRKL is an oncogene in multiple cancers. Consistent with the data from previous papers that CRKL expression correlates with poor prognosis, Prognoscan, a publicly available database, indicates that high expression of CRKL may serve as a poor prognostic factor for liposarcoma and lung adenocarcinoma patients (Fig. S9).…”
Section: Discussionsupporting
confidence: 89%
“…CRKL amplification was previously observed in non‐small cell lung and gastric cancers, strongly suggesting that CRKL is an oncogene in multiple cancers. Consistent with the data from previous papers that CRKL expression correlates with poor prognosis, Prognoscan, a publicly available database, indicates that high expression of CRKL may serve as a poor prognostic factor for liposarcoma and lung adenocarcinoma patients (Fig. S9).…”
Section: Discussionsupporting
confidence: 89%
“…Accumulating evidence has been reported and suggested that dysfunction of CRKL as a key factor in variety of human diseases, including inflammation and carcinomas [1820]. In our previous study, we also validated CRKL as a promoter in GC, induces GC cells proliferation and motility.…”
Section: Discussionsupporting
confidence: 63%
“…CCR7 is expressed by gastric cancer cells, with higher levels of CCR7 expression associated with lymph node metastasis, higher stage tumor, and poor overall survival. Treatment of human gastric cancer cells with CCL19 induced the expression of MMP-9 and decreased levels of E-cadherin, consistent with a shift towards a pro-metastatic phenotype (Cheng, Guo, Yang, & Yang, 2015). In ovarian cancer, CCR7 + tumor status was also correlated with advanced disease stage and with lymph node metastasis, and these clinical parameters were linked to increased expression of MMP-9 and N-cadherin (Cheng et al, 2014) that were subsequently determined to be dependent upon CCL19 signaling (Cheng et al, 2015).…”
Section: Cues For Tls Developmentmentioning
confidence: 74%